(untitled) (Research, Society and Development, 2023)
Objective: The present study presented the objective of analyzing the speeches of students of the undergraduate nursing course at the State University of Ceará (UECE), on the use of "virtual rooms" as a pedagogical teaching strategy in the context of the COVID-19 pandemic. Method: This is an exploratory and descriptive study with a quantitative and qualitative approach. The survey was carried out online, by sending the link to the google forms questionnaire and a total of 40 students participated. Results: The results showed that as positive points in virtual classes, students highlighted: use of technologies as learning strategies; flexibility and customization of the teaching-learning process; university protagonism; real-time class in which students actively participate. And as negative points: difficulty in establishing a daily routine for studies; reliance on technology for live classes; internet connection problems during classes; decreased interaction and socialization of those involved; lack of student participation during remote classes; and impossibility of carrying out practical classes that require health services and/or laboratories. Conclusion: Knowing the students’ perception of virtual classes in the nursing course helped to demystify the implementation of disciplines in the health area, expanding the construction of disciplines around TDIC’s, making it possible to contribute to the formation of university students, using active methodologies that improve nursing education and encourage shared autonomy between students and professors.